Carbon turnover and microbial activity in an artificial soil under imposed cyclic drainage and imbibition. Issue 1 (1st April 2020) - Pronk, Geertje J.; Mellage, Adrian; Milojevic, Tatjana; Smeaton, Christina M.; Engel, Katja; Neufeld, Josh D.; Rezanezhad, Fereidoun; Van Cappellen, Philippe
Abstract: Water table fluctuations generate temporally and spatially dynamic physicochemical conditions that drive biogeochemical hot spots and hot moments in the vadose zone. However, their role in the cycling of soil C remains poorly known. Here, we present results from unvegetated column experiments filled with 45 cm of artificial soil containing 10% humus, and inoculated with a natural microbial extract. In one series of three replicate columns, five cycles, each consisting of a 4‐wk drainage followed by a 4‐wk imbibition period, were imposed, whereas in a second series, the water table remained static. Depth‐resolved O2 concentration profiles and headspace CO2 effluxes were markedly different between the two regimes. In the fluctuating regime, drainage periods yielded 2.5 times greater CO2 effluxes than imbibition periods. At the end of the experiment, the fluctuating water table columns exhibited a distinct zone of organic C (OC) depletion in the depth interval of 8–20 cm that was not observed under the static regime. Although this zone showed elevated levels of adenosine triphosphate (ATP), the microbial biomass was actually lower than at the corresponding depth interval of the static regime. A vertically stratified microbial community established in all columns that depended on oxygenation with depth. The 16S ribosomal RNA (rRNA) gene analyses showed a slightly higher diversity in the soil exposed to moisture fluctuations, but there was no clear difference in major taxa and microbial community composition between treatments. These results thus suggest that the localized enhancement of OC degradation induced by the water table fluctuations was driven by a more active, rather than a more abundant or compositionally very different, microbial community. Core Ideas: Artificial soil columns were incubated with natural soil microbial inoculum. Replicates were subjected to cycles of drainage and imbibition. Drainage after water‐logged conditions led to pronounced pulses of CO2 efflux. Incubation treatment yielded distinct zone of OC depletion in the fluctuation zone. Enhanced turnover was driven by more active and not more diverse biomass community.